Approche textométrique de l’articulation du discours narratorial et des discours directs dans un corpus de contes du XVIIe siècle - Catherine Boré; Denise Malrieu (Discours)
This paper aims to characterize the modes of articulation of narratorial discourse and direct speech in a collection of 17th century tales: a tale by Madame d’Aulnoy (The Pigeon and the Dove, 20,840 words) and tales by Perrault (20,641 words). The editions used were printed when direct speech was not typographically marked. To characterize the tales, we analyzed the interaction between the introductory segments, interpolated clauses and punctuation.   To observe the internal or relational properties of the reported speech categories, textometric tools were applied on the previously tagged texts and their components and relative positions were linguistically qualified.   We first compared the main type of narrator discourse chosen in each corpus, based on the relative importance of each type of reported speech. This initial analysis highlighted significant differences in the distribution of these speech types between Perrault and Madame d’Aulnoy.   Textometric analysis was then carried out to characterize the different modalities used to introduce direct speech. The syntactic properties of the boundaries between narrator discourse and direct speech were studied, depending on whether there was an introductory segment in the left context of the direct speech or whether there was an interpolated clause.   We showed that Madame d’Aulnoy’s text is characterized by the absence of introductory segments in the direct speech. The differentiation of the direct speech will then be marked by using allocutive modalities, indexicality, the address and the interpolated clause. We showed the vicarious feature of the interpolated clause and the introductory segment, and the direct speech’s function of object complement of their speech verbs. Then we analyzed the place of the interpolated clause in the direct speech and its closing punctuation, and we showed that the interpolated clause could be continued by the narratorial speech without rupture, and that it was part and parcel of the latter.